Coping with Maternal Deaths: The Experiences of Midwives - Dartey, Anita Fafa (Ethiop J Health Sci, 2019)
BACKGROUND: Life is said to be meaningful only when the individual is able to cope with challenges associated with it. Challenges at the workplace, whether physical, psychological or social, all contribute to occupational trauma. Coping with the challenges of work is an important part of achieving occupational wellbeing, irrespective of how difficult the job may be. Midwives are trained to be responsible for safe motherhood. However, when faced with maternal deaths, work becomes difficult as they have to cope with trauma resulting from their encounters with these deaths. Thus, the aim of this study was to explore and describe the coping challenges of maternal deaths among midwives in the Ashanti Region of Ghana. METHOD: An exploratory descriptive qualitative design was used in the study. Data were collected by means of semi-structured interviews (18) and focus group discussions (8) with inclusion criteria of being a midwife with at least one year working experience and having witnessed maternal death while on duty. Data were audio recorded, transcribed and analysed using thematic content analysis. RESULTS: Four themes emerged from the study: difficulty accepting maternal death, exhibition of grief reactions, difficulty forgetting the deceased and lack of concentration. CONCLUSION: The study concluded that since the midwife's ability to cope with maternal deaths is challenged, occupational workplace programmes, for example, Employee Assistance Programme (EAP) should be employed in Ghanaian hospitals to help midwives get debrief after maternal death occurs.